Academic Advising process Roles in supporting student’s success - Al-Khafaji, Dr. Salah (International Journal of Scientific Research and Management (IJSRM), 2017)
The Academic Advising program is a continued support system that provides supervision to the students for registering, adding and dropping of their selection of courses, according to their chosen study plan. It also shows them how to study effectively and efficiently to gain the academic achievements they desire. By following the Academic Advisors supervision and regulations of this program, they will have a much better opportunity to fulfill their academic achievements to the highest standards possible.  Finally, the “Academic Advising guide lines” provided by the Advisors are intended to assist the students in improving their CGPA, and in the graduation process. This is in accordance to the study plan set to be within the mutually accepted period of time to complete the accredited programs, courses and curriculum needed for graduation to enable future employment opportunities. The supporting of the students to acquire the knowledge and skill set required for the students graduation is the “main” goal of the Academic Advising Program and its advisors.The academic advising process provide guidance to students so that they may achieve their academic objectives, and through a careful monitoring of their degree plans, ensure that they conform to the various rules and regulations and assist them to overcome any obstacles that might impede the successful completion of their degree.  In order to progress smoothly through their degree plans, students need to have accurate information about subject requirements and how to fulfill them